Pengaruh Pemberian secara Subkronik Minyak Atsiri Daun Sirsak (Annona muricata Linn.) terhadap Kadar Low Density Lipoprotein (LDL) dan High Density Lipoprotein (HDL) Serum Tikus Wistar - Yunita Ika Pratiwi; Sasi Purwanti; Dini Sri Damayanti (Published by Faculty of Medicine Universitas Islam Malang, 2017)
Introduction: The essential oil of soursop (Annona muricata Linn.) leaves contains terpenoid, alkaloid, and phenolic compounds. Terpenoid, alkaloid and phenolic function as antioxidants and antiinflammatory agents appropriately. When used in high concentrations and in long period, it may become toxic, which mayincreasein LDL and decrease in HDL. The study is to determine the safety of soursopleaf essential oil on LDL and HDL levels in wistar rats.Methods: This was an invivo experimental study with a control group post test only design using 20 male and 20 female wistar rats divided into 8 groups, consisting of KN (tween 80), P1 (1,25 mg/kgBW), P2 (2,5 mg/kgBW), and P3 (5mg/kgBW) both male and female rats. This study was conducted for 28 days then the LDL and HDL levels were checked after the treatment. Results were analized using One Way ANOVA test followed by Least Significant Difference (LSD). Results are assumed significant if p<0.05.Results and discussion: Administration of soursop leaf essential oil in P1 group showed the highest LDL levels and a higher dose of soursop leaf essential oil will cause a lower LDL levels in both male and female groups. The P2 group showed the highest HDL levels and P3 group had decreased HDL levels compared to P2 group in both male and female groups. The increasing of LDL levels and the decreasing of HDL levels in all treatment groups, is suspected to be caused by active compounds in soursop leaf essential oil, body weight differences and food consumption differences on rats.Conclusion: The doses between 1,25 to 5 mg/kgBW is considered to be safe, in which no increase in LDL and decrease in HDL in normal male and female rats was observed.Keywords: Essential oil of soursop leaves,Annona muricata Linn., Subchronic,LDL,and HDL.